2001
DOI: 10.1002/mrm.1117
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a rapid clearance blood pool MR contrast medium (P792) for assays of microvascular characteristics in experimental breast tumors with correlations to histopathology

Abstract: The diagnostic potential of a new rapid clearance blood pool contrast medium (P792; MW ‫؍‬ 6.47 kDa) for the MR assessment of microvessel characteristics was assessed in 42 chemicallyinduced breast tumors, with comparisons to albumin-(Gd-DTPA). Microvessel characteristics, including the transendothelial permeability (K PS ) and the fractional blood volume (fPV), were estimated by using dynamic MR data fit to a bidirectional twocompartment model. The MR-derived estimates for K PS and fPV using each contrast age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 33 publications
4
36
1
Order By: Relevance
“…Several authors have used P792 to characterize tumor physiology in animal models. Turetschek et al found no relation between transendothelial permeability estimated with P792 and histologic parameters (microvessel density and tumor grade) in a breast cancer model (32). In a prostate cancer model, however, P792-based DCE-MRI was successfully used to monitor changes in permeability after anti-VEGF therapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have used P792 to characterize tumor physiology in animal models. Turetschek et al found no relation between transendothelial permeability estimated with P792 and histologic parameters (microvessel density and tumor grade) in a breast cancer model (32). In a prostate cancer model, however, P792-based DCE-MRI was successfully used to monitor changes in permeability after anti-VEGF therapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI was performed using a T 1 -weighted 3D gradient-echo sequence (TR ϭ 10. Quantitative analysis of albumin-(Gd-DTPA) 30 -enhanced MRI data was based on a two-compartment, unidirectional pharmacokinetic model, which assumes no reflux of the macromolecular contrast material (MMCM) from the tumor interstitium into the vascular compartment during the time course of the imaging experiment (30,31). Details regarding the pharmacokinetic analysis of the DCE-MRI data have been previously described (9).…”
Section: Mri Studiesmentioning
confidence: 99%
“…A quantitative analysis of the albumin-(Gd-DTPA) 30 -enhanced imaging data was based on a two-compartment, unidirectional pharmacokinetic model (15,16):…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…For small molecular contrast media (SMCM) like gadopentetate, high temporal resolution is required in order to separately extract estimates of these factors from the kinetic data (13,14). With the combined use of macromolecular contrast media (MMCM) and a unidirectional two-compartment kinetic model (15,16), the fractional plasma volume and the PS-limited endothelial transfer constant can be simultaneously determined (17). The microvascular blood flow rates need not be known.…”
mentioning
confidence: 99%